Sinergi Amanah dan Tawakal dalam Ketahanan Bisnis Zero-Supervision: Reflesksi Kritis Teori Agensi dan Homo Economicus - Risno Ibrahim; Anton Bawono; Wahyu Wibowo (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This research examines the business phenomenon of a Zero-Supervision canteen at UIN Sunan Kalijaga Yogyakarta, which remarkably survives despite operating without formal supervision and facing daily financial losses. The research aims to analyze the synergy between Amanah (trustworthiness) and Tawakal (spiritual reliance) in sustaining business resilience (value resilience), while critically reflecting on Agency Theory and the Homo Economicus assumption. Using a qualitative single case study approach, data were collected through in-depth interviews with 13 informants—students and the canteen owner—and supported by direct observation. The findings reveal that Amanah, driven by spiritual accountability, functions as an internal control mechanism that substitutes formal supervision and significantly reduces agency costs, approaching zero-agency cost. Meanwhile, Tawakal serves as a spiritually grounded risk management strategy that enables the business owner to tolerate uncertainty and financial losses without jeopardizing business continuity. The synergy of these values forms a holistic resilience model that extends beyond financial metrics to encompass ethical, social, and spiritual dimensions. This study provides empirical evidence that spiritual capital plays a fundamental role in sustaining micro-businesses and offers a critical challenge to conventional economic models rooted solely in rational self-interest.